The Novel Map - Bray, Patrick (Northwestern University Press, 2021)
Focusing on Stendhal, Gérard de Nerval, George Sand, Émile Zola, and Marcel Proust, The Novel Map: Mapping the Self in Nineteenth-Century French Fiction explores the ways that these writers represent and negotiate the relationship between the self and the world as a function of space in a novel turned map.